Tobacco Smoking During Pregnancy Is Associated With Increased Risk of Moderate/Severe Bronchopulmonary Dysplasia: A Systematic Review and Meta-Analysis - Gema E. González-Luis; Elke van Westering-Kroon; Eduardo Villamor-Martinez; Maurice J. Huizing; Mohammed A. Kilani; Boris W. Kramer; Eduardo Villamor (Frontiers Media S.A., 2020)
Epidemiological evidence and animal studies support that intrauterine exposure to tobacco smoke disturbs lung development and has a negative effect in the pulmonary health of the offspring. Individual studies suggest an association between fetal exposure to maternal smoking and risk of developing bronchopulmonary dysplasia (BPD). However, this association has not yet been systematically investigated. We aimed to conduct a systematic review of studies reporting on tobacco smoking during pregnancy as potential risk factor for BPD. PubMed/MEDLINE and EMBASE databases were searched. BPD was defined as requirement of supplemental oxygen on postnatal day 28 (BPD28; all BPD), at the postmenstrual age (PMA) of 36 weeks (BPD36; moderate/severe BPD), or as requirement of more than 30% oxygen and/or positive pressure at 36 weeks PMA (severe BPD). Pooled risk ratios (RR) and 95% confidence intervals (CI) were calculated using a random-effects model. Of 2,894 potentially relevant studies, 33 met the inclusion criteria. The included studies evaluated 171,772 infants and included 30,445 cases of exposure to maternal smoking and 25,340 cases of BPD of any severity. Meta-analysis showed a significant association between tobacco smoking during pregnancy and BPD36 (17 studies, RR 1.126, 95% CI 1.008-1.259, p = 0.036), but could not demonstrate a significant association between tobacco smoking during pregnancy and BPD28 (16 studies, RR 1.021, 95% CI 0.924-1.129, p = 0.681), or severe BPD (3 studies, RR 1.143, 95% CI 0.528-2.478, p = 0.734). In conclusion, our data suggest that tobacco smoking during pregnancy increases the risk of moderate/severe BPD. Our results highlight the detrimental effects of tobacco smoking and reinforce the hypothesis of the involvement of prenatal insults in the etiopathogenesis of BPD.